Pulmonary Sarcoidosis following Etanercept Treatment for Ankylosing Spondylitis: A Case Report and Review of the Literature - Majjad, A. (Case Rep Rheumatol, 2018)
Antitumor necrosis factor therapies have revolutionized the treatment of some inflammatory diseases. However, the use of these agents is associated with the development of many paradoxical autoimmune diseases. Less well-recognized is the association with sarcoidosis. We report a 55-year-old female with long-standing ankylosing spondylitis who developed persistent dry cough and dyspnea while receiving etanercept therapy. High-resolution computed tomography scanning showed mediastinal lymphadenopathy and multiple nodules in both lung fields developed two months after the administration of etanercept. Lymph node biopsy was not practicable. Histopathological examination of minor salivary gland biopsy revealed noncaseating granulomata, and the serum angiotensin-converting enzyme was very elevated. All infectious studies were negative. Etanercept was discontinued plus a course of corticosteroids with a clinical improvement, and a follow-up high-resolution computed tomography scanning 4 months later showed evident regression of mediastinal lymph nodes and pulmonary nodules. Potential pathogenic mechanisms of this paradoxical effect of tumor necrosis factor-alpha blocking agents are discussed.